Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi dan Pengendalian Internal Terhadap Akuntabilitas Kinerja Instansi Pemerintah dengan Kualitas Laporan Keuangan sebagai Variabel Moderasi - Nur Al-Fidha; Sumarlin; Namla Elfa Syariati (Indonesian Journal of Taxation and Accounting, 2025)
This study aims to examine the effect of budget target clarity, accounting control and internal control on government agency performance accountability with the quality of financial reports as a moderating variable. This study was conducted in SKPD Makassar City. This study uses a quantitative approach with a questionnaire survey method. The sample in this study was 140 people consisting of heads of divisions and all members of the planning, reporting and finance sections in 27 Regional Work Units (SKPD) of Makassar City using purposive sampling techniques. Data were collected using questionnaires and analyzed using multiple regression analysis and Moderate Regression Analysis (MRA). The results of the study indicate that budget target clarity does not affect government agency performance accountability while accounting control and internal control variables have a positive and significant effect on government agency performance accountability. Meanwhile, the quality of financial reports is able to moderate accounting control and internal control on government agency performance accountability, but is unable to moderate budget target clarity on government agency performance accountability. The implications of this study reflect an important contribution in encouraging improvements in governance, especially in terms of transparency and accountability of financial management and government agency performance. Thus, this research is expected to not only be a technical reference for the government in building a more efficient and effective system, but also as a normative basis for strengthening the openness of public information.